Effect of two cytokinins and a growth inhibitor on the in vitro tuberization of two genotypes of Solanum tuberosum L. cvs. Atlantic and Alpha - Garcia, Jose Antonio (2019)
This investigation was carried out to evaluate the effect of two cytokinins: 6-benzilaminopurine (BAP) (6.5 mg l-1) and kinetin (K) (2.5 mg l-1), as well as the growth inhibitor abscisic acid (ABA) (1.0 mg l-1) on the in vitro tuberization capacity of two potato varieties: Atlantic and Alpha. The basal culture medium MS (1962) was used as a control. The responses were different between varieties. In cv. Atlantic, the analysis of the number (NM), weight (WM) and diameter (DM) of microtubers indicated that the addition of growth regulators did not affect induction and development of microtubers. However, when BAP was used, a non-significant increment of 41 % was observed in the number of the microtubers compared to the control treatment, from 2.6 to 4.4. The addition of cytokinins and ABA to the medium did not have a significant impact on the development of microtubers. In cv. Alpha the cytokinins used without ABA increased the number of microtubers, which were larger and heavier than those of the control treatment. In this variety, ABA significantly reduced the values of the NM, WM and DM variables. The exogenous action of cytokinins in the culture medium is likely to have caused an endogenous hormonal imbalance in the Atlantic and Alpha genotypes which interfered with their innate microtuberization ability, a result that was even more evident for cv. Alpha, which showed the need to continue optimizing protocols of genotype-specific systems in potato tissue culture to increase yield and seed quality.